PENGARUH FILTER AKTIF TERHADAP LOSSES TRANSFORMATOR DI FAKULTAS TEKNIK UNIVERSITAS UDAYANA BUKIT JIMBARAN DENGAN FUZZY LOGIC CONTROLLER MENGGUNAKAN SIMULINK - Indra Jana Martana, I Kadek; Arta Wijaya, I Wayana; Suartika, I Made (Jurnal SPEKTRUM, 2023)
Harmonics in the electrical system can have a negative impact on the quality of the electrical energy being distributed. Harmonics are phenomena that arise due to the operation of non-linear electrical loads. Thus causing the formation of waves with a frequency that is different from the fundamental frequency. Total harmonic distortion (THD) is the effective value of waves affected by harmonics so that they can affect power losses. This study analyzes the power losses in the KA4214 transformer at the Faculty of Engineering, Udayana University, Bukit Jimbaran. The method used is to carry out simulations and analysis of the results of harmonic measurements carried out in existing conditions using active filters, and using active filters with fuzzy logic controllers and then compared with IEEE 519-2014 standards. The simulation results from using an active filter with a fuzzy logic controller obtained the smallest current THD value of each phase, namely R = 0.28%, S = 0.71% and T = 0.72% with the resulting power losses of 0.0009905 kW.